Produksi dan Fisiologi Kedelai pada Kondisi Cekaman Kekeringan dengan Aplikasi Bradyrhizobium japonicum yang Diberi Penginduksi Genistein - Hasanah, Yaya; Rahmawati, Nini (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTMutualism symbiosis between B. japonicum and soybean root is a complex case and managed by molecular signal exchange. Genistein is one of the main isoflavones in soybean root exudates which is responsive to nod gen induction in B. japonicum. Drought stress could give negative effect on the symbiosis. The aim of the research was to study the role of B. japonicum induced by genistein on production and physiological characters of soybean under drought stress. The experiment was conducted in a green house, Faculty of Agriculture, University of Sumatera Utara, using a randomized complete block design with three factors. The first factor was genistein induction, consisted of with and without genistein. The second factor was B. japonicum inoculation consisted of without B. japonicum, isolate 1, isolate 2 and isolate 3. The third factor was soil water content condition, consisted of 40%, 60% and 80% of field capacity. The parameters observed were shoot dry weight, root dry weight, net assimilation rate, dry weight per plant, 50 seeds weight and proline content. The result showed that increasing drought stress conditions decreased shoot dry weight, root dry weight, net assimilation rate, effective nodules number, seeds dry weight per plant and 50 seeds weight. The result showed that as an inducer of B. japonicum in drought stress condition, genistein reduced the effects of water stress on root nodulation of soybean. Proline acts as osmoregulator for increasing tolerance to drought stress in plants.Keywords: drought, genistein, soybean, root nodulation